Respuesta :
Answer:
[tex]x=10[/tex]
Step-by-step explanation:
1) Subtract 10 from both sides of the equation
[tex]9x+10=11x-10\\9x+10-10=11x-10-10[/tex]
2) Simplify
a. Subtract the numbers
b. Subtract the numbers again
[tex]9x=11x-20[/tex]
3) Subtract 11x from both sides of the equation
[tex]9x=11x-20\\9x-11=11x-20-11x[/tex]
4) Simplify
a. Combine like terms
b. Combine like terms again
[tex]-2x=-20[/tex]
5) Divide both sides of the equation by the same term
[tex]-2x=20\\\frac{-2x}{-2} =\frac{-20}{-2}[/tex]
6) Simplify
a. Cancel terms that are in both the numerator and denominator
[tex]\frac{-2x}{-2} =\frac{-20}{-2} \\x=\frac{-20}{2}[/tex]
b. Divide the numbers
[tex]x=\frac{-20}{-2x} \\x=10[/tex]
Simplifying
9x + 10 = 11x + -10
Reorder the terms:
10 + 9x = 11x + -10
Reorder the terms:
10 + 9x = -10 + 11x
Solving
10 + 9x = -10 + 11x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-11x' to each side of the equation.
10 + 9x + -11x = -10 + 11x + -11x
Combine like terms: 9x + -11x = -2x
10 + -2x = -10 + 11x + -11x
Combine like terms: 11x + -11x = 0
10 + -2x = -10 + 0
10 + -2x = -10
Add '-10' to each side of the equation.
10 + -10 + -2x = -10 + -10
Combine like terms: 10 + -10 = 0
0 + -2x = -10 + -10
-2x = -10 + -10
Combine like terms: -10 + -10 = -20
-2x = -20
Divide each side by '-2'.
x = 10
Simplifying
x = 10
9x + 10 = 11x + -10
Reorder the terms:
10 + 9x = 11x + -10
Reorder the terms:
10 + 9x = -10 + 11x
Solving
10 + 9x = -10 + 11x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-11x' to each side of the equation.
10 + 9x + -11x = -10 + 11x + -11x
Combine like terms: 9x + -11x = -2x
10 + -2x = -10 + 11x + -11x
Combine like terms: 11x + -11x = 0
10 + -2x = -10 + 0
10 + -2x = -10
Add '-10' to each side of the equation.
10 + -10 + -2x = -10 + -10
Combine like terms: 10 + -10 = 0
0 + -2x = -10 + -10
-2x = -10 + -10
Combine like terms: -10 + -10 = -20
-2x = -20
Divide each side by '-2'.
x = 10
Simplifying
x = 10